Scientific effect of pranayama (hatha yogic breath regulation techniques) on physiological and psychological variables: A systematic review - Kesar; Neeru Nathani (Yoga-Mimamsa)
Pranayama, a fundamental practice of traditional Hatha Yoga, has been recognized for centuries as a profound science of breath regulation. It encompasses a range of breathing techniques to enhance physical, mental, and spiritual well-being. This systematic review explores the scientific effect of Pranayama (Hatha yogic breathing techniques), including Nadishodhana, Suryabhedan, Ujjayi, Sheetkari, Sheetali, Bhastrika, and Bhramari. This review aims to explore the scientific evidence regarding the impact of Pranayama on physiological and psychological variables and overall quality of life (QoL). In addition, it examines the potential therapeutic applications of these techniques in managing chronic health conditions. For this review, data were obtained using a stepwise search process, which involved searching PubMed and PubMed Central online databases from January 2000 to December 2024. Keywords related to various Pranayama were used for this search. Studies were screened based on their titles, abstracts, and full texts for inclusion, focusing on those reported physiological and psychological outcomes with relevant parameters. The database search identified 1112 articles, which yielded 185 after filtration. Out of them, 145 were excluded for not meeting the research objectives. A total of 40 full-text articles were assessed and ultimately 20 studies were included in this review. These studies have demonstrated a significant effect of Pranayama on various physiological and psychological variables and overall QoL. Available evidence suggests that various types of Pranayama can significantly improve physiological and psychological well-being. These practices have the potential to enhance overall QoL. Incorporating Pranayama into our daily routines promotes a healthier lifestyle.